Desarrollo de una aplicación móvil de promoción de las principales obras pictóricas de los artistas cotopaxenses empleando la metodología “mobile-d en la Casa de la Cultura Benjamín Carrión núcleo de Cotopaxi - Montatixe Granada, Jhonatan Patricio (2022)
Technological update is carried out at cultural centers around the country to promote the Casa de la Cultura Benjamín Carrión Núcleo de Cotopaxi joining this process and use technology, the present work proposes to improve users’ experience to have an optimized content, a personalization of information being what is needed and differentiation through development of a mobile application oriented to promote the most relevant pictorial works of Cotopaxi artists. The development of the mobile application which will be carried on behalf of CCE Museum was a requirement of this cultural center which will facilitate knowing pictorial works and more relevant information that applicant requires to be projected on CCE Museum app: exhibition of the museums, art gallery, archaeological and popular art, historical information and location.